Competition Law Paradigm in the Majapahit Constitution - Faizal, Bhismoadi Tri Wahyu; Amin, Muhammad; Sidiq, Muhammad Aunurrofiq; Nurmawati, Reni Prasetia (Faculty of Law Universitas Trunojoyo Madura, 2025)
This paper aims to map and analyze business activities potentially resulting in monopolistic practices and unfair business competition in the Majapahit kingdom. This research also attempts to figure out how the rule of law was applied during the Majaphit kingdom to curb monopolistic business activities. This research applied a qualitative design with normative legal or library research that relies on secondary data sources. Primary legal materials in this research are two ancient books by Slamet Muljana, namely Majapahit Legislation and Nagarakretagama Historical Interpretation; secondary legal materials are books and journals related to this research. The results show that 4 (four) types of activities can lead to monopolistic practices and unfair business competition, namely, destroying or burning agricultural land, reducing farm yields, refusing others to do the same business and controlling land owned by small farmers by large farmers. For these activities, the Majapahit royal government imposed the rule of law contained in Articles 260 - 262 of the Kutaramanawa and Article 88 paragraph (3) of the Nagarakretagama which includes a prohibition on burning and destroying agricultural land, a ban on reducing agricultural yields by narrowing the land or leaving the land abandoned, a prohibition on refusing others to work on the land, and a prohibition on large farmers to control the land of small farmers. The government in the Majapahit era demonstrated how the law should be implemented, and that it should be emulated by modern countries, including Indonesia, to enforce the country’s welfare by encouraging vigorous and competitive law in Indonesia.